Krisis Pembentukan Sumber Daya Manusia Berbasis Konsep Maslahah: Mengatasi Kesenjangan Kualitas di Era Digital - Riswandha Ipnu Nawawi; Ridho Apriyadi; Romlah; Ali Abdul Wakhid (Mataram University, 2026)
The world of Islamic boarding schools currently faces a major challenge in aligning traditional values ​​with the demands of global competence. This journal analyzes the crisis of human resource formation in Islamic boarding schools that causes a gap in the quality of graduates in the digital era. Using the Maslahah framework, this study explores how Islamic boarding schools can transform without losing their identity. This study aims to formulate a Human Resource Crisis Based on the Maslahah Concept as an effective strategy in maintaining the welfare of the public and educational institutions. Through literature studies and qualitative analysis of cases of human resource crises in the quality gap in the digital era, this model proposes five pillars of communication in maslahah: Speed ​​and Informative Honesty (Hifz al-'Aql), Decisions that Guarantee the Safety of Life (Hifz al-Nafs), Fair and Transparent Resource Allocation (Hifz al-Mal), Strengthening Solidarity and Public Morality (Hifz al-Din and Hifz al-Nasab), and Restoring Long-Term Welfare. The results of the study indicate that the integration of digital literacy based on Maqasid al-Shariah is a strategic solution to close this quality gap, so that Islamic boarding school graduates are able to become agents of change that are relevant to the needs of the times while still upholding the principle of the welfare of the people.